Application of Ultrasonic Velocity Profiler (UVP) in the Crude Oil Emulsion Pipeline Flow - Fan, Wong Siew; Dol, Sharul Sham (Advanced Aspects of Engineering Research Vol. 15, 2021)
The formation of emulsions is undesirable in the oil and gas industry because emulsification brings a number of problems; it affects the flow regimes and flow behavior, reduces the crude oil’s quality, occupies a volume in the pipeline, reduces the mass flow rate, requires longer retention time in the separation vessels, causes corrosion to the transport system, contaminates catalyst used in the refining process and increases operating cost. Yet, this is unavoidable because oil will always be produced together with water from the reservoir and towards the end of the reservoir life, with the increasing amount of water especially if the reservoir is driven by water aquifer. Less attention has been paid to the pipeline flow of water-in-oil (W/O) emulsions. Therefore, one of the attempts of this research work is to investigate the formation of W/O emulsions using a continuous flow loop, where the emulsification process is induced by the flow shear and turbulence effects such as the pipeline constriction disturbance in the flow loop. The experimental part of this research study is conducted using a model lab-scale continuous flow rig with the present of a 90° bend pipeline constriction and Bintulu crude oil is used. The experiments is focusing on studying the flow velocity and the turbulence role in the formation of emulsions by using an ultrasonic velocity profiler (UVP) system. The roles of turbulence in the formation of emulsions can be understood from the UVP study. This will then broadly contribute to the transportation of crude, i.e. with less emulsions formation, as the energy for the formation of emulsions can be controlled accordingly with the understanding on the roles of turbulence activities in the emulsification process.